A Method for Generating Approximate Similarity Solutions of Nonlinear Partial Differential Equations. (22nd July 2014) - Iqbal, Mazhar; Mustafa, M. T.; Siddiqui, Azad A.
Abstract : Standard application of similarity method to find solutions of PDEs mostly results in reduction to ODEs which are not easily integrable in terms of elementary or tabulated functions. Such situations usually demand solving reduced ODEs numerically. However, there are no systematic procedures available to utilize these numerical solutions of reduced ODE to obtain the solution of original PDE. A practical and tractable approach is proposed to deal with such situations and is applied to obtain approximate similarity solutions to different cases of an initial-boundary value problem of unsteady gas flow through a semi-infinite porous medium.